The oldest estimated age for roughtail stingray [Dasyatis centroura (Mitchill, 1815)] from the Mediterranean Sea - Basusta, N.; Sulikowski, J. A. (Wiley-Blackwell, 2012)
[Abstract Not Available]
Keywords: Rhinobatos-Rhinobatos; Common Guitarfish; Growth; Pisces; Turkey